Threshold switching of a NbOx device prepared by DC reactive sputtering. (23rd May 2019) - Nakajima, Ryo; Azuma, Atsushi; Shimizu, Tomohiro; Ito, Takeshi; Shingubara, Shoso
Abstract: Threshold switching devices based on insulator-metal transition (IMT) are expected to overcome the reduction of sneak current and studies of their use for self-oscillators attract much attention. In this study, we observed threshold switching caused by IMT in a cross-point Pt/Ti/NbOx /Pt/Ti/SiO2 device after annealing at 400 °C, annealing assisted formation of stable stoichiometric NbO. The diffusion of Ti atoms of thetop electrode to the NbOx layer was observed. It is suggested that Ti oxidation caused scavenging of oxygen from NbOx, and valence number of Nb ion is reduced to form stoichiometric metallic NbO. With applying negative voltage to the upper Pt/Ti electrode, a NbO2 layer was formed by diffusion of oxygen ions from the TiOx layer. Then threshold switching has become easy to occur in the succeeding positive voltage sweeping.